2018
DOI: 10.1016/j.cllc.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Ventana ALK (D5F3) in the Detection of Patients Affected by Anaplastic Lymphoma Kinase-positive Non–Small-cell Lung Cancer: Clinical and Budget Effect

Abstract: Patients with anaplastic lymphoma kinase-positive (ALK D) advanced nonesmall-cell lung cancer should benefit from targeted therapy. The effect of increased use of an immunohistochemical technique was estimated using a health careeeconomics analysis. Extensive use of D5F3 has resulted in a diagnostic costs decrease. These savings could be reinvested to test a greater number of patients (53% vs. 75%). Reinvesting the saving would lead to an overall survival gain (D20%). Background: To ensure identification of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…The relationship between NSCLC tissue sample processing and labour intensity in the Italian setting was previously highlighted 16 , 17 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The relationship between NSCLC tissue sample processing and labour intensity in the Italian setting was previously highlighted 16 , 17 .…”
Section: Resultsmentioning
confidence: 95%
“…A 5-year budget impact analysis proved the Ventana ALK (D5F3) CDx assay to reduce the oncologists’ work load in detecting ALK positive NSCLC patients eligible to crizotinib 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Doshi et al [ 10 ] concluded that both in the United States (U.S.) and Europe, ALK testing only by IHC is the lower-cost strategy compared with using only FISH, reflex testing, or performing both tests in parallel. Paolini et al [ 13 ] assessed the clinical and economic benefits of using IHC for ALK rearrangement testing in Italy, and concluded that increased use of D5F3 would provide savings of € 468,000, due to its lower acquisition cost compared with FISH and a comparable detection rate. Lu et al [ 60 ] evaluate the cost-effectiveness of the ALK tests followed by crizotinib compared to the standard chemotherapy in advanced NSCLC from the Chinese healthcare system perspective.…”
Section: Discussionmentioning
confidence: 99%
“…For some years, FISH has been the reference standard for detecting tumors carrying ALK rearrangement. However, growing evidence has shown that IHC testing is an efficient tool in the detection of ALK rearrangement, and confirmation of positive results by FISH is no longer needed [ 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since they were not present in the literature, it was not possible to compare these results with those of other evaluations, with the sole exception of those of a recent study conducted on the determination of the ALK mutation in NSCLC patients [30]. According to the authors, a greater use of a specific immunohistochemical test (Ventana ® ), compared to other tests and FISH, would allow to increase the correct identification of the ALK+ mutation, with a consequent increase in the overall survival from 27.1 months to 32.4 months.…”
Section: Discussionmentioning
confidence: 99%